2016
DOI: 10.21548/28-1-1459
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment of Distillery Wastewater after UASB using Aerobic Techniques

Abstract: The treatment of high-strength wastewater from a distillery using grape-based feedstock was conducted through sequencing the upflow anaerobic sludge blanket (UASB) reactor and the aerobically-activated sludge reactors. The performance of the UASB system was evaluated at the end of a period of 33 days in terms of the final chemical oxygen demand (COD) removal. Final COD removal efficiency of up to 88.7% was achieved. The effect of varying the volumetric loading rates on COD removal was evaluated for the two exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…There are a number of anaerobic treatments including anaerobic lagoons, fixed bed reactors, fluidised beds and anaerobic membrane bioreactors (Satyawali and Balakrishnan, 2008) however one of the most widely used anaerobic techniques used for the treatment of high strength organic effluents is the upflow anaerobic sludge blanket (UASB) (Musee et al, 2016). It has been successfully applied in treating a number of industrial effluents including: Palm oil mill effluent (Lee, 2006); Paper mill wastewater (Kamali et al, 2016); Distillery wastewater (Musee et al, 2016); dairy wastewater (Tawfik et al, 2008); fishery wastewater (Huang et al, 2009); slaughterhouse wastewater (Chavez et al, 2005); Piggery effluent (Huang et al, 2005) and municipal wastewater (Rivzi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of anaerobic treatments including anaerobic lagoons, fixed bed reactors, fluidised beds and anaerobic membrane bioreactors (Satyawali and Balakrishnan, 2008) however one of the most widely used anaerobic techniques used for the treatment of high strength organic effluents is the upflow anaerobic sludge blanket (UASB) (Musee et al, 2016). It has been successfully applied in treating a number of industrial effluents including: Palm oil mill effluent (Lee, 2006); Paper mill wastewater (Kamali et al, 2016); Distillery wastewater (Musee et al, 2016); dairy wastewater (Tawfik et al, 2008); fishery wastewater (Huang et al, 2009); slaughterhouse wastewater (Chavez et al, 2005); Piggery effluent (Huang et al, 2005) and municipal wastewater (Rivzi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully applied in treating a number of industrial effluents including: Palm oil mill effluent (Lee, 2006); Paper mill wastewater (Kamali et al, 2016); Distillery wastewater (Musee et al, 2016); dairy wastewater (Tawfik et al, 2008); fishery wastewater (Huang et al, 2009); slaughterhouse wastewater (Chavez et al, 2005); Piggery effluent (Huang et al, 2005) and municipal wastewater (Rivzi et al, 2015). The UASB is deemed to be particularly reliable reactor performance regularly achieving COD removal efficiencies in excess of 80% and biogas CH 4 concentration in excess of 50% for a range of wastewaters and reactor specifications (Latif et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the activated sludge process treats biodegradable organic material in domestic sewage as well as effluents from other sources such as pulp and paper mills, food industries, abattoirs, textile mills, edible oils, coal gasification wastes, petrochemical wastes, and oil refinery wastes (Henze et al, 2002;Metcalf and Eddy, 2002). The sorption of pollutants on activated sludge is among the fundamental processes for the removal of toxic substances including metals, synthetic organic chemicals, suspended solids, and pathogens in wastewater (Dobbs et al, 1989;Musee et al, 2007;Sheng et al, 2008). However, the sorption process may be ineffective as the bacteria used for wastewater treatment can be inhibited by toxic substances, e.g., heavy metals (Çeçen et al, 2010), thus adversely impacting the biologically-based treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to organisations constructing AD plants to achieve various waste management targets and renewable energy goals (Bekkering et al, 2016) A popular form of treatment for medium to high strength effluents is Upflow Anaerobic Sludge Blankets (UASBs) (Musee et al, 2016), which have demonstrated high reliability both in terms of their COD removal efficiencies (typically >80%) and biogas CH 4 concentrations (typically >50%) (Latif et al, 2011). This performance has been documented in a number of studies treating a wide range of wastewaters including: Palm oil mill effluent (Siang, 2006); Paper mill wastewater (Kamali et al, 2016); Distillery wastewater (Musee et al, 2016); dairy wastewater (Tawfik et al, 2008); fishery wastewater (Huang et al, 2009); slaughterhouse wastewater (Chavez et al, 2005); Piggery effluent (Huang et al, 2005) municipal wastewater (Rivzi et al, 2015), malting's steep water (Borzacconi et al, 2006) and malt ingredients factory wastewater (Cairns and Mead, 2017).…”
Section: Introductionmentioning
confidence: 99%